Retinal degenerative diseases - LaVail, Matthew M. (Advances in experimental medicine and biology,, 2012)
This book will contain the proceedings of the XIV International Symposium on Retinal Degeneration (RD2010), held July 13-17, 2010, in Mont-Tremblant, Quebec, Canada. The volume will present representative state-of-the-art research in almost all areas of retinal degenerations, ranging from cytopathologic, physiologic, diagnostic and clinical aspects; animal models; mechanisms of cell death; candidate genes, cloning, mapping and other aspects of molecular genetics; and developing potential therapeutic measures such as gene therapy and neuroprotective agents for potential pharmaceutical therapy.